A study on the AMACR catalysed elimination reaction and its application to inhibitor testing. Issue 2 (5th November 2015) - Yevglevskis, Maksims; Lee, Guat L.; Sun, Jenny; Zhou, Shiyi; Sun, Xiaolong; Kociok-Köhn, Gabriele; James, Tony D.; Woodman, Timothy J.; Lloyd, Matthew D.
Abstract : The elimination of fluoride from 3-fluoro-2-methylacyl-CoA substrates by α-methylacyl-CoA racemase (AMACR 1A; P504S) was investigated as a method for determining enzyme activity and inhibitor potency. Abstract : α-Methylacyl-CoA racemase (AMACR; P504S) catalyses a key step in the degradation of branched-chain fatty acids and is important for the pharmacological activation of Ibuprofen and related drugs. Levels of AMACR are increased in prostate and other cancers, and it is a drug target. Development of AMACR as a drug target is hampered by lack of a convenient assay. AMACR irreversibly catalyses the elimination of HF from 3-fluoro-2-methylacyl-CoA substrates, and this reaction was investigated for use as an assay. Several known inhibitors and alternative substrates reduced conversion of 3-fluoro-2-methyldecanoyl-CoA by AMACR, as determined by 1 H NMR. The greatest reduction of activity was observed with known potent inhibitors. A series of novel acyl-CoA esters with aromatic side chains were synthesised for testing as chromophoric substrates. These acyl-CoA esters were converted to unsaturated products by AMACR, but their use was limited by non-enzymatic elimination. Fluoride sensors were also investigated as a method of quantifying released fluoride and thus AMACR activity. These sensors generally suffered from high background signal and lacked reproducibility under the assay conditions. In summary, the elimination reaction can be used to characterise inhibitors, but it was not possible to develop a convenient colorimetric or fluorescent assay using 3-fluoro-2-methylacyl-CoA substrates.